1988
DOI: 10.1113/jphysiol.1988.sp016916
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of two types of calcium currents to the pacemaker potentials of rabbit sino‐atrial node cells.

Abstract: constantly hyperpolarized. The bradyeardia was caused mainly by a reduction in the rate of depolarization in the later phase of the pacemaker depolarization. The bradyeardia elicited by nickel was due neither to blockade of the hyperpolarizationactivated inward current nor to inhibition of the delayed rectifier potassium current.9. It was concluded that the transient type calcium channel exists in the cardiac nodal cell and that the current participates in the later half of the slow diastolic depolarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
532
5
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 745 publications
(573 citation statements)
references
References 34 publications
35
532
5
1
Order By: Relevance
“…Spontaneous contractions of smooth muscle cells were observed between days 1 and 3 in small networks containing cells with ICC-like appearance (e.g., triangular cell bodies and multiple processes) and with smooth muscle-like appearance (7,13,17). Positive immunoreactivity with the anti-c-kit antibody ACK2 confirmed that the cultures contained ICC.…”
Section: Resultsmentioning
confidence: 79%
“…Spontaneous contractions of smooth muscle cells were observed between days 1 and 3 in small networks containing cells with ICC-like appearance (e.g., triangular cell bodies and multiple processes) and with smooth muscle-like appearance (7,13,17). Positive immunoreactivity with the anti-c-kit antibody ACK2 confirmed that the cultures contained ICC.…”
Section: Resultsmentioning
confidence: 79%
“…Such a calcium current, classically observed in vertebrate cardiac tissue (Hagiwara et al 1988) has been identified in other molluscs (Curtis et al 1999;Ö dblom et al 2000;Pennec et al 2004). L-type channel, in molluscs as in lower vertebrates, is thought to be the primary pathway for Ca 2?…”
Section: Discussionmentioning
confidence: 80%
“…Early studies found that LVA channels were more sensitive to block by 50 -100 M nickel than HVA channels (124,152,298). Subsequent studies found that many neuronal T-type channels required Ͼ10-fold higher concentrations for block, with many studies reporting IC 50 values of ϳ300 M ( Table 2).…”
Section: Isolated Neuronsmentioning
confidence: 99%